The role of the Organizational Service Orientation practices and its Impact in inhancing the employees performance (A Fiald Research in Baghdad Municipality) - عبد الوهاب نادية لطفي; علي مرتضى عبد الحسن (Journal of Economics and Administrative Sciences, 2016)
Abstract: Recently, there is a widespread attention about the service at the level of each of the research and academic studies, and at the organizational level as well. The subject of orientation towards the service aspect is starting to be of this attention being of the modern subjects, relatively, which appeared at the end of the last century, as well as the link of this subject with the relationship between the organization and its customers, and how to provide high quality services to get their satisfaction. Thus, the specialists from researchers were interested in this field to develop an appropriate scale to measure the organizational orientation toward service, and it was the most prominent of these scales, the scale (SERV * OR) provided by (Lytle et al 1998), and adopted by many authors in their research, many of the organizations, and various work environments. The research is applied to in offices of Secretariat of Baghdad and adopted a sample of (240) persons, including different management levels and disciplines in the Secretariat. This research aims to identify the dimensions of organizational orientation towards service, that is more important in the Secretariat or Municipality of Baghdad, and their impact in enhancing the performance of employees, and the extent of interest of offices of Secretariat of Baghdad to provide approporate services to the customers, and realize its employees of responsibilities entrusted them to provide these services satisfactorily to their customers. So, the research found that senior management in the Secretariat is keen to deliver a vision of service clearly to all employees, and this is shown by the search results dramatically. But most of the powers confined to the managers in the Municipality of Baghdad, and the employees havenot sufficient powers to work independently to provide services to customers. It was one of the research recommendations is to make the Baghdad Municipality to empower their employees to take appropriate decisions, which helps to overcome the problems and complaints of customers (citizens), and show it in a set of actions that illustrate and highlight the attention of the Secretariat to provide quality services to their customers, and the completion of their applications as soon as possible, as well as interest of their grievances and problems, and try to find the appropriate solutions quickly, and thus makes them feel good about the services provided.